Proteome analysis of clustered helicobacter pylori strains - Vitoriano, Inês (2012)
Genomic-methylation typing method, based on strains’ Restriction/Modification systems, confirmed the genetic variability of Helicobacter pylori. According to this, strains isolated from patients of the same family, or from the same geographic region, cluster together. The analysis of proteome’s variability of these clusters has been a missing topic. We applied the Minimum-Common-Restriction-Modification (MCRM) algorithm to genomic-methylation data of 30 H. pylori strains, isolated from Portuguese patients, presenting different gastric diseases. 100% of generated dendrograms presented three incipient clusters (C1, C2 and C3), which is characteristic of strains sharing the geographic origin. The same pattern was observed when the MCRM algorithm was applied to a subset of strains (2 of C1, 2 of C2, 4 of C3 and two outsiders). These were heterogeneous regarding their cagA and vacA genotypes and in terms of patient’s age, gender and gastric disease. Comparative analysis of two-dimensional-gel-electrophoresis (2-DE) maps, obtained for total-protein extracts of each strain, revealed that among 70 matched protein spots (in a universe of 300), 16 were differently abundant (p < .05) among clusters. These proteins’ abundance was then compared having the 2DE-maps regrouped according to the strain’s cagA-genotype or its association with gastric disease. We concluded that abundance variations of at least 12 proteins were dictated by differences in virulence, rather than cluster proximity. Therefore, although the genome-methylation typing method discriminates differences in restriction/modification enzymes, strains of each generated cluster do not share a marked particular proteome, arguing that strains with common geographic origin vary greatly in virulence.